Perceptions of Child Sexual Abuse: The Effects of Perpetrator Age, Rural Status, and Rape Myth Acceptance - Gruenfelder, Kalynn C (2021)
Child sexual abuse (CSA) is a global issue, affecting many children in the short- and long-term. Despite the high prevalence of CSA, factors affecting adults’ perceptions of CSA are still in question. Research focuses on CSA committed by adults, but there is disproportionately less research examining perceptions of CSA committed by juveniles. Research shows a higher incidence of juvenile-perpetrated CSA than adult-perpetrated CSA in the lifetime of 17-year-olds (Finkelhor, Shattuck, Turner, & Hamby, 2014). The current study aimed to fill the gaps in the literature concerning adult perceptions of CSA cases considering victim and perpetrator characteristics and rape myth acceptance. More specifically, the current study examined adult perceptions of the depiction of abuse, severity of CSA, culpability, revictimization, and future well-being of the victim based on perpetrator age using vignettes. Consistent with predictions, participants rated sexual abuse perpetrated by older offenders as more severe than abuse committed by younger perpetrators and non-rural participants rated CSA depictions as more severe than rural participants. Contrary to hypotheses, the community sample rated CSA as more severe compared to students. In addition, non-rural participants blamed the victim more and endorsed rape myths more than rural participants. This study also examined the interaction between the age of the perpetrator/initiator and acceptance of rape myths, such that the effect of perpetrator/initiator age on participants’ perceptions of the sexual contact in the vignettes depended on stereotyped attitudes about sexual assault. Results showed the effect of perpetrator age on perceptions of severity of abuse strengthened and weakened in relation to changes in the moderating variable (i.e., rape myth acceptance). Finally, this study explored participants’ adherence to crime stereotypes. As hypothesized, of participants who misremembered the perpetrator in the vignette as being depicted with a gender, most misremembered the perpetrator’s gender as male. Implications for these findings are provided